Curriculum Innovation Management in MAN Middle Tapanuli District - Lubis, Muhammad Ali Napiah; Wijaya, Candra; Halimah, Siti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of this research is to discuss curriculum innovation management in Man, Central Tapanuli Regency (Multi-Site Study in MAN in Central Tapanuli Regency). This research uses a multi-site qualitative method where data collection techniques include interviews, observation, and document study techniques. Meanwhile, to strengthen the validity of the data found and the authenticity of the research, the researcher refers to the use of data validity standards suggested by Lincoln & Guba, which consist of credibility, transferability. , dependability, and comfirmability. The results of this research are: Curriculum innovation planning at MAN Central Tapanuli Regency has several aspects, including: a) always improving the quality of education both from an academic and non-academic perspective; b) being a superior madrasah with unique skills. c) Having new ideas or ideas related to the emergence of curriculum innovation local load (MULOK); d) Having a goal so that students are able to live and have life skills, an entrepreneurial, national, and religious spirit; and e) Having graduates and opportunities that are accepted by the community based on the foundation of ahlussunnah wal jama'ah; 2). The implementation of Curriculum Innovation at MAN in Central Tapanuli Regency has several similarities, namely: a) Both use the same curriculum base, namely referring to BSNP, b) Carry out curriculum development in religious subjects, c) Collaborate with other institutions to improve the quality of students in in the field of skills, d) Conducting stady comparisons with Madrasahs or other institutions as a consideration for improving education, e) Organizing structured worship practices for students to improve quality in the religious field, f) Encouraging students to remain disciplined in their behavior and administration, and g ) Hold direct practice in activities related to skills and sports; 3). The evaluation of curriculum innovation in MAN Central Tapanuli Regency is carried out gradually, either every semester or every month. B). The evaluation agenda is carried out by the Madrasah leadership with the theme of Madrasah self-evaluation (EDM) in the educational staff area. Curriculum waka evaluation is carried out incidentally with the theme of curriculum activity materials (review) in each department. Teacher evaluation is carried out in stages for educational curriculum innovation in madrasas.